2021
DOI: 10.1016/j.esmoop.2021.100133
|View full text |Cite
|
Sign up to set email alerts
|

High BRAF variant allele frequencies are associated with distinct pathological features and responsiveness to target therapy in melanoma patients

Abstract: Background: BRAF mutant melanoma patients are commonly treated with anti-BRAF therapeutic strategies. However, many factors, including the percentage of BRAF-mutated cells, may contribute to the great variability in patient outcomes.Patients and methods: The BRAF variant allele frequency (VAF; defined as the percentage of mutated alleles) of primary and secondary melanoma lesions, obtained from 327 patients with different disease stages, was assessed by pyrosequencing. The BRAF mutation rate and VAF were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
1
10
1
Order By: Relevance
“…However, the V600E incidence rate described in this cohort (69/5384, 1.28 %) was slightly lower, but broadly in line with other published data, in keeping with which V600E was the single most commonly detected mutation [8]. BRAF mutation VAF was highly heterogeneous across all three mutation classes, which is broadly in line with findings in patients with melanoma [9], though the significance of the lower mean VAF in Class I mutations is uncertain.…”
Section: Discussionsupporting
confidence: 90%
“…However, the V600E incidence rate described in this cohort (69/5384, 1.28 %) was slightly lower, but broadly in line with other published data, in keeping with which V600E was the single most commonly detected mutation [8]. BRAF mutation VAF was highly heterogeneous across all three mutation classes, which is broadly in line with findings in patients with melanoma [9], though the significance of the lower mean VAF in Class I mutations is uncertain.…”
Section: Discussionsupporting
confidence: 90%
“…These different median allele frequency rates of pathogenic KRAS mutations between short-and long-term PDAC survivors might be explained by the role of KRAS mutations in inducing tumor progression, with tumors showing higher allele frequency rates for pathogenic KRAS mutations, i.e., tumors harboring a higher proportion of KRAS-mutated subclones, showing a faster tumor progression, hence its link to early disease recurrence in our study. The impact of the allele frequencies of pathogenic mutations on patient outcome has already been evaluated in other solid malignancies, e.g., in malignant melanoma [43].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, controversial results have been obtained by studies which related the BRAF V600E MAF of melanoma tumors with clinicopathological and prognostic characteristics as well as the melanoma response, in order to target therapies [15,[23][24][25][26]. All these studies analyzed the MAF value of one specific region for each tumor, so we wanted to know whether the variation degree of BRAF V600E MAF within different regions of the same tumor could influence these characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the usefulness of the BRAF V600E driver mutation as a therapeutic target, a recent study has suggested that the mutational load of BRAF V600E is a possible prognostic biomarker [15], expanding the classical histopathological prognostic criteria such as ulceration, Breslow, Clark or mitotic indexes [1,[16][17][18][19][20][21][22]. Moreover, some studies in recent years have attempted to relate the mutational load to the response in order to target therapies, but controversial results have been obtained [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%